Gambaran Ketangguhan Mental Atlet Universitas Malikussaleh - Utami, Rahayu Setya; Suzanna, Ella; Anastasya, Yara Andita (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
Mental toughness is a positive emotional reaction, especially in Malikussaleh University athletes to overcome all pressure in the training process and matches. This research aims to determine the dimensions that shape the mental toughness of Malikussaleh University athletes and the factors that influence the mental toughness of Malikussaleh University athletes. This research uses a qualitative method with a phenomenological approach. Data collection uses interview, observation and documentation techniques. The research results show that based on the overall dimensions, athletes are able to control themselves against internal and external pressure when on the field, are confident in their physical and mental abilities, have a responsible attitude, never give up and make many sacrifices while being athletes such as sacrificing time, finances, energy and education. Based on factors, overall athletes are influenced by time discipline, persistence in training, self- confidence and listening to directions from the coach.